Optimal scheduling of integrated energy system based on green certificate-carbon trading fusion mechanism (International Conference on Energy, Intelligence Systems, and Cloud Computing (Ingenio 2026), 2026)
To address the challenge of low-carbon economic operation in multi-energy coupled regional integrated energy systems, this paper proposes a source-load complementary optimal scheduling model based on the integration of green certificates and stepped carbon trading. First of all, an integrated mechanism of green certificate and stepped carbon trading is introduced to enhance the consumption capacity of renewable energy on the source side and cut down the carbon emissions of the system. Secondly, incentive-based demand response and peak-shaving revenue are incorporated on the load side to achieve the “peak shaving and valley filling” of thermoelectric loads. Finally, the CPLEX solver is adopted to solve the model with the objective of minimizing the daily operating cost. The results demonstrate that the integrated mechanism of green certificate and stepped carbon trading is conducive to giving full play to the optimization capacity of incentive-based demand response, improving the absorption capacity of renewable energy on the source side, realizing coordinated carbon reduction on both the source and load sides, reducing the system’s operating cost, and effectively enhancing the greenness, low-carbon performance and economy of the system operation.
Keywords: Source-load complementarity; Green electricity certificate; Stepped carbon trading; Fusion mechanism; Optimized scheduling